The Role of the Nursing Committee on the Quality of Nursing Services - Yolanda Anastasia Sihombing; Nur Syamsi Norma Lala; Muh. Ihsan Kamaruddin (Jurnal Edukasi Ilmiah Kesehatan, 2023)
The Nursing Committee plays an important role in improving the quality of nursing services. The committee's role includes the development and review of nursing policies and procedures, monitoring and evaluation of nursing practice, training, and professional development, collaboration between nurses and health teams, and advocacy for nurses and patients. This study aims to determine the role of the nursing committee in the quality of nursing services. Quantitative research design with cross-sectional analytical descriptive approach. The results show a p-value; of 0.043 which states the influence of the role of the nursing committee on the quality of nursing services. It can be concluded that researchers reveal a relationship between the role of the nursing committee and the quality of nursing services. The role of an effective Nursing Committee can contribute positively to improving the quality of nursing services.